De onde os pais olham seu bebê? : um estudo acerca do olhar dos pais diante de um caso situado entre o autismo e a adoção - Carvalho, Vívian Batista de (2014)
During the first months of life, a baby shows an intense interest in looking and being looked at, but when it does not happen and the mother does not realize this fact, we can consider it as a sign of risk of autism (Laznik, 2004). Thus the clinic with babies proposes a treatment of children since the moment that the first elements that indicate psychological distress appear. This way, the gaze of the parents is crucial in early clinical intervention, which aims to mental health in early childhood and its implications for later life. This study was developed in this direction, starting from our clinical activities, with babies who have some psychological distress, realized in parents-babies groups at CAPSi Early Intervention Center of Campina Grande state of Paraiba. Our general goal was to analyze the place in which these parents put themselves face the adoption of a baby with indicative signs of autism. As specific goals, we proposed: to investigate how this baby is spoken by their parents, since the gaze may be an effect of the word, and we also intended to articulate the issues that led to the adoption and to the signs of autism. We took as basis for our work the psychoanalytic theoretical reference, having as the primary driver of our readings the literary work of Freud and Lacan. We also emphasized texts of other authors that talk about the constitution of the subject and the early clinical intervention for children at risk of autism or facing difficulties in establishing the parent-infant bond. A case study was conducted to illustrate the issue of the parents‟ gaze, emphasizing from which place the baby is seen, at which point of Lacan's optical scheme their parents are located. We also discussed issues related to adoption, motherhood and fatherhood. Related data were collected through interviews with the mother, the father and two professionals who provide care to the baby, besides consulting the patient records.